Taxonomy and Biology of Calonectria in Brazil - Alfenas, Rafael Ferreira (2013)
Species of the genus Calonectria (= Cylindrocladium) are important pathogens in a wide range of host plants, particularly in tropical and subtropical climates. Most of the diseases caused by species of Calonectria are associated mainly with plants of Fabaceae (Acacia spp.), Myrtaceae (Eucalyptus spp.) and Pinaceae (Pinus spp.). Nowadays there are about 76 species of Calonectria that are recognized based mainly on morphology and phylogenetic inference. Taxonomic studies on these fungi have chiefly relied on DNA sequences comparisons of the β- tubulin gene region. However calmodulin (CAL) and translation elongation factor 1- alpha (TEF-1α) gene regions have been shown best resolution for the identification of new species in Calonectria. Based on TEF-1α sequence analysis of 1017 isolates collected from samples of plants and soils in different regions of Brazil, it was demonstrated that Calonectria spp. studied belong to six complexes. Among these C. pteridis, C. brassicae, C. morganii, C. scoparia, and C. naviculata complexes contain 28 new species here described. Calonectria pteridis complex predominates (87%) on eucalypt plantations in Brazil. According to morphological features and multigenic phylogenetic analysis of β-tubulin (TUB2), histone H3 (HIS3), calmodulin (CAL) and the elongation factor (TEF-1α) genes 28 new Calonectria species were described. Moreover, in this study 17 species of eucalypt (Eucalyptus and Corymbia) were evaluated for resistance to calonectria leaf blight (CLB). Eucalyptus aglomerata, E. brassiana, E. saligna, and E. scias were the most resistant and E. tereticornis, E. pilularis, C. maculata, E. grandis, E. dunii, and C. citriodora the most susceptible species.